ACCEPTING THE OMEN: EXTERNAL REFERENCE IN GREEK DECLAMATION. (17th July 2017) - Guast, William
Abstract : Traditional accounts of Greek declamation paint this important imperial genre as a flight from the alleged impotence of Greek cities under Roman rule into a nostalgic fantasy of the autonomy of the classical past. But there is clear evidence of declaimers using their works to refer to the world outside the fiction, often to the immediate performance context, and above all to themselves. This paper examines examples from Aelius Aristides, Philostratus' Lives of the Sophists and Polemo, and shows that such a practice facilitated vigorous and eloquent communication, while also allowing for any external message to be plausibly denied.